Psychosomatic health status and corresponding comorbid network analysis of college students in traditional Chinese medicine schools - Yi, Shuang; Hu, Xingang; Wang, Chengzhe; Ge, Jieqian; Ma, Zixiang; Zhao, Yan (Frontiers in Psychiatry, 2024)
Introduction: Depression, anxiety, and somatic symptoms are highly comorbid and represent the most prevalent psychosomatic health issues. Few studies have investigated the network structure of psychosomatic symptoms among traditional Chinese medicine (TCM) students. This study aims to investigate the psychosomatic health status of college students in TCM universities, while simultaneously constructing a network structure of common somatic symptoms and psychological symptoms.Methods: Online investigation was conducted among 665 students from a university of Chinese medicine. Health Status Questionnaire, Generalized Anxiety Disorder-7 (GAD-7), and Patient Health Questionnaire-2 (PHQ-2) were used to assess the mental symptoms and physical status of participants. With the R software processing, a network model of psychosomatic symptoms was constructed. Specifically, we computed the predictability (PRE), expected influence (EI), and bridging expected influence (BEI) of each symptom. Meanwhile, the stability and accuracy of the network were evaluated using the case-deletion bootstrap method.Results: Among the participants, 277 (41.65%) subjects exhibited depressive symptoms, and 244 (36.69%) subjects showed symptoms of anxiety. Common somatic symptoms included fatigue, forgetfulness, sighing, thirst, and sweating. Within the psychosomatic symptoms network, " worrying too much about things ", "uncontrollable worries" and "weakness" exhibited the high EI and PRE, suggesting they are central symptoms. " Little interest or pleasure in doing things," " feeling down, depressed, or hopeless," " dyssomnia," and "sighing" with high BEI values demonstrated that they are bridging symptoms in the comorbid network.The psychosomatic health status of college students in traditional Chinese medicine schools is concerning, showing high tendencies for depression, anxiety, and somatic symptoms. There exists a complex relationship between somatic symptoms and psychological symptoms among students. " Worrying too much about things ", "uncontrollable worries" and "weakness" enable to serve as comorbid intervention targets for anxiety, depression, and somatic symptoms. Addressing " little interest or pleasure in doing things," " feeling down, depressed, or hopeless," " dyssomnia," and "sighing" may effectively prevent the mutual transmission between psychological and physical symptoms. The network model highlighting the potential targeting symptoms to intervene in the treatment of psychosomatic health.